Depth-dependent dynamics of liquid metal surfaces with first principles simulations. (1st October 2020) - del Rio, Beatriz G.; González, Luis E.
Graphical abstract: Abstract: Liquid metal surfaces have gained increased interest over the last decade due to new applications in synthesis of 2D materials, catalysis, or fusion reactors. Static properties such as the reflectivity and density profile have been determined, both experimentally and computationally, for numerous liquid metals and alloys. However, the characterization of the dynamic properties has remained a challenging task and only one experimental study by Reichert et al. has evaluated the depth-dependence of different dynamic properties in the liquid indium (l-In) surface. In this paper, we present an ab inito molecular dynamics study of the collective dynamic properties of this same system at different depths, obtaining very good agreement with the experimental data. In addition, we are able to compute the properties much closer to the surface than experimentally attainable, and have discovered that at these shallower depths, the properties drastically differ from those deeper in the slab. Therefore, this study sheds light into the behavior of dynamic properties at the atomic interface and highlights the ability of ab initio molecular dynamics to study such unknown dynamic behavior of liquid metals surfaces at depths not yet attainable experimentally but of crucial importance for liquid surface physics.